De novo loss‐of‐function mutations in X‐linked SMC1A cause severe ID and therapy‐resistant epilepsy in females: expanding the phenotypic spectrum. Issue 5 (14th February 2016) - Jansen, S.; Kleefstra, T.; Willemsen, M.H.; de Vries, P.; Pfundt, R.; Hehir‐Kwa, J.Y.; Gilissen, C.; Veltman, J.A.; de Vries, B.B.A.; Vissers, L.E.L.M.
Abstract : De novo missense mutations and in‐frame coding deletions in the X‐linked gene SMC1A (structural maintenance of chromosomes 1A), encoding part of the cohesin complex, are known to cause Cornelia de Lange syndrome in both males and females. For a long time, loss‐of‐function (LoF) mutations in SMC1A were considered incompatible with life, as such mutations had not been reported in neither male nor female patients. However, recently, the authors and others reported LoF mutations in females with intellectual disability (ID) and epilepsy. Here we present the detailed phenotype of two females with de novo LoF mutations in SMC1A, including a de novo mutation of single base deletion [c.2364del, p.(Asn788Lysfs*10)], predicted to result in a frameshift, and a de novo deletion of exon 16, resulting in an out‐of‐frame mRNA splice product [p.(Leu808Argfs*6)]. By combining our patients with the other recently reported females carrying SMC1A LoF mutations, we ascertained a phenotypic spectrum of (severe) ID, therapy‐resistant epilepsy, absence/delay of speech, hypotonia and small hands and feet. Our data show the existence of a novel phenotypic entity – distinct from CdLS – and caused by de novo SMC1A LoF mutations. Abstract :